1993
DOI: 10.1126/science.7694370
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Tyrosine Phosphorylation for Rapid Activation of a DNA Binding Factor by IL-4

Abstract: Interleukin-4 (IL-4) is an immunoregulatory cytokine produced by activated T lymphocytes to promote the growth and differentiation of cells that participate in immune defense. This study demonstrates the rapid activation of a specific DNA binding factor by IL-4. The IL-4 nuclear-activated factor (IL-4 NAF) appeared within minutes of IL-4 stimulation and recognized a specific DNA sequence found in the promoters of IL-4-responsive genes. Activation of this putative transcription factor required tyrosine phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
147
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(153 citation statements)
references
References 38 publications
5
147
0
1
Order By: Relevance
“…Early work on IL-4 signal transduction suggested that IL-4 signaling would parallel the general STAT pathway described above (Kohler and Rieber, 1993;Kotanides and Reich, 1993;Schindler et al, 1994). For example, IL-4, like other cytokines, had been found to induce rapid and speci®c gene activation events within hours of cytokine stimulation.…”
Section: Structural Characteristics Of Stat6mentioning
confidence: 99%
See 1 more Smart Citation
“…Early work on IL-4 signal transduction suggested that IL-4 signaling would parallel the general STAT pathway described above (Kohler and Rieber, 1993;Kotanides and Reich, 1993;Schindler et al, 1994). For example, IL-4, like other cytokines, had been found to induce rapid and speci®c gene activation events within hours of cytokine stimulation.…”
Section: Structural Characteristics Of Stat6mentioning
confidence: 99%
“…The protein that bound to the site was tyrosine phosphorylated in response to IL-4 and shared homology with other known STAT proteins in its proposed DNA binding, SH3 and SH2 domains. The protein was termed by several groups STF-IL-4, IL-4 STAT, IL-4 NAF and ultimately Stat6 (Hou et al, 1994;Kotanides and Reich, 1993;Quelle et al, 1995;Schindler et al, 1994).…”
Section: Structural Characteristics Of Stat6mentioning
confidence: 99%
“…Each of these is activated by specific stimuli. STAT6 was originally identified as a gamma-activated sequence binding protein in extracts derived from interleukin (IL)-4-treated cell lines (Kotanides and Reich, 1993;Hou et al, 1994;Schindler et al, 1994). Accordingly, IL-4 can specifically induce tyrosine phosphorylation of STAT6.…”
Section: Introductionmentioning
confidence: 99%
“…In ®broblasts, IL-4 modulates functional responses such as extracellular matrix production (Postlethwaite et al, 1992) and chemotaxis (Postlethwaite and Seyer, 1991), rather than inducing pronounced proliferative e ects (Postlethwaite et al, 1992). IL-4R activation (Wang et al, 1992) results in tyrosine phosphorylation of many signaling molecules including Jak1, Jak3 (Johnston et al, 1994;Witthuhn et al, 1994), IRS-1 (Wang et al, 1993b), IRS-2/4PS (Wang et al, 1993a), and Stat6 (Hou et al, 1994;Kotanides and Reich, 1993;Quelle et al, 1995;Schindler and Darnell, 1995). In Stat6 de®cient mice, IL-4-induced proliferation of T cells as well as B cells after IgM stimulation was dramatically reduced (Kaplan et al, 1996;Shimoda et al, 1996;Takeda et al 1996).…”
Section: Introductionmentioning
confidence: 99%